Strategi Guru Bimbingan dan Konseling dalam Menangani Masalah Siswa yang Sering Membolos dan Terlambat di SMP Negeri 1 Tigo Nagari (International Forum of Researchers and Lecturers, 2025)
Student truancy and tardiness are serious problems that impact students' academic achievement and social-emotional development. This study aims to examine the strategies implemented by Guidance and Counseling (BK) teachers in dealing with students who often truant and are late at SMP Negeri 1 Tigo Nagari. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the strategies implemented include early identification of at-risk students, strengthening teacher-student relationships, ongoing counseling services, parental involvement, implementation of group guidance, and consistent enforcement of regulations. These strategies have proven effective in reducing the level of student absence and tardiness. This study concludes that the role of BK teachers is very important in creating a school environment that supports student discipline and involvement. These findings are expected to be a reference for other schools in developing a systematic and collaborative guidance approach.